Surveillance of Drinking Water of Karachi City: Microbiological Quality (Biological Sciences - PJSIR, 2008)
In the analysis of 329 treated (tap) water samples and 30 well water samples of Karachi city, 94 (28.5%) tap water samples were found contaminated with faecal coliforms and had high heterotrophic plate count (HPC), 153 (46.5%) had very high heterotrophic plate count and only 82 samples were fit for human consumption. Out of 30 well water samples only 2 samples were fit for human consumption; 23 (76%) had high faecal coliform count and HPC, whereas, 5 (16.67%) were rejected owing to extremely high bacterial count.